2018
DOI: 10.1109/jstqe.2018.2846044
|View full text |Cite
|
Sign up to set email alerts
|

Dengue E protein detection using graphene oxide integrated tapered optical fiber sensor

Abstract: We report the use of a biofunctionalized tapered optical fiber based sensor with the integration of graphene oxide (GO) for the detection of Dengue virus (DENV) II E proteins. The tapered region was deposited with GO and functionalized with anti-DENV II E protein IgG antibodies to be tested with different concentrations of DENV II E proteins. The sensor obtained a detection limit of 1 pM with a sensitivity value of 12.77 nm/nM, which was better compared to previously reported studies. The sensor also showed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…In particular, handling with high control the dispersion and waveguiding properties of the microstructured core and inner cladding regions allow the maximization of evanescent field based sensing and the integration of the interferometric geometry. Further applications will be possible in the next future thank to the recent advances on glasses/optical fibers operating in MiD-IR [50,51,52] where several biomolecules and polluting contaminants exhibit their spectral fingerprint and the development of novel PCF sensors and lasers are expected with the aim to extend the operation wavelength range of devices for biomedicine application [14,22,39,53].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, handling with high control the dispersion and waveguiding properties of the microstructured core and inner cladding regions allow the maximization of evanescent field based sensing and the integration of the interferometric geometry. Further applications will be possible in the next future thank to the recent advances on glasses/optical fibers operating in MiD-IR [50,51,52] where several biomolecules and polluting contaminants exhibit their spectral fingerprint and the development of novel PCF sensors and lasers are expected with the aim to extend the operation wavelength range of devices for biomedicine application [14,22,39,53].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of graphene oxide (GO) instead of graphene is considered a good trade-off between properties of graphene characteristics and the synthesis cost/difficulty. A wide range of GO chemical sensors, biosensors and gas sensors have been proposed [34,35,36,37,38,39]. In [38] a GO coated photonic crystal fiber (PCF) has been fabricated to obtain a modal Mach-Zehnder interferometer for strain and temperature sensing.…”
Section: Coated Pcf Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, two well-known optical sensors have been used to identify and quantify the dengue virus, i.e., the tapered optical fiber (TOF) and the surface plasmon resonance (SPR) sensors. A study using TOF revealed the successful detection of dengue virus (DENV) at 1 pM within 15 min [15]. However, this sensor requires precise alignment, high cleanliness and maintenance, and very careful handling, since the fibers can break easily [16,17].…”
Section: Introductionmentioning
confidence: 99%